1969
DOI: 10.1002/star.19690211102
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Scattering by Single Starch Granules

Abstract: Potofo 0 > 10 20 30 LO 50 60 70 80 90 Fa c h z e i t s c h r if t f iir Er f o r s chung, Hers t e l l u n g u nd Verwendung yon Starke und S t a r k e e r z e u g n i s s e n I00 Schriftleitung: Ernst Hees, 532 Bad Godesberg, DeutschherrenstraJe 40 IVISSENSCHAFTLICHE VERLAGSGESELLSCHAFT kl.B,H., STVTTGART, BIRKEKIVALDSTRASSE 44 JAHRGAKG 21 1969 Nr. 11

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1
1

Year Published

1971
1971
1992
1992

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 5 publications
1
8
1
1
Order By: Relevance
“…This may be due to the fact that FALS and absorbance of light by cells and cellular components has been shown to be affected by variables (i. e. particles asymmetry, refractive index, , and reflective properties) that are not directly related to size [ll]. In addition, it has been shown that some large particles scatter less light than theoretically expected [12]. Thus, the ' appearance of granules in a step or pulse-like pattern rather than a tight linear function my be due to differences in morphological or internal structure differences within each size class.…”
Section: Analysis Of Starch Granulesmentioning
confidence: 99%
“…This may be due to the fact that FALS and absorbance of light by cells and cellular components has been shown to be affected by variables (i. e. particles asymmetry, refractive index, , and reflective properties) that are not directly related to size [ll]. In addition, it has been shown that some large particles scatter less light than theoretically expected [12]. Thus, the ' appearance of granules in a step or pulse-like pattern rather than a tight linear function my be due to differences in morphological or internal structure differences within each size class.…”
Section: Analysis Of Starch Granulesmentioning
confidence: 99%
“…3 in Ref. 1). The presence and clarity of these maxima is important, because as will be shown later, the relative scattered intensity distribution among them is much more sensitive to internal morphology of the granule than is the primary cloverleaf.…”
Section: H Scatteringmentioning
confidence: 87%
“…The quantitative intensity distribution of the pattern in Figure 8 is shown in Figure 9, to be compared with the calculated theoretical distribution for a perfectly spherical and homogeneously anisotropic granule, shown in a,)(SiUsin U ) -(atar) cos2 (812) cos2 p X (4 sin U -U cos U -3SiU)I2 @) where as is the polarizability of the surrounding matrix and other quantities have the same significance as in cq. (1) .' It is apparcnt from the above equation that only the third term in brackets depends on the anisotropy of the spherulite.…”
Section: Scatteringmentioning
confidence: 99%
“…Quantitative density measurements on the latter films were performed with a *Vertically polarized incident beam, analyzer with polarization direction horizontal. Joyce-Loebl microdensitometer as previously described [4] . All computations were performed on an IBM 1620-11 computer.…”
Section: Methodsmentioning
confidence: 99%